2012
DOI: 10.1186/2049-1891-3-26
|View full text |Cite|
|
Sign up to set email alerts
|

Progress of genome wide association study in domestic animals

Abstract: Domestic animals are invaluable resources for study of the molecular architecture of complex traits. Although the mapping of quantitative trait loci (QTL) responsible for economically important traits in domestic animals has achieved remarkable results in recent decades, not all of the genetic variation in the complex traits has been captured because of the low density of markers used in QTL mapping studies. The genome wide association study (GWAS), which utilizes high-density single-nucleotide polymorphism (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 51 publications
0
62
0
10
Order By: Relevance
“…The former was 16 bp downstream of an ankyrin repeat and the SOCS box containing 3 (ASB3) gene and 46 bp upstream of the endoplasmic reticulum lectin 1 (ERLEC1) gene. Using the same approach, the study conducted by Zhang et al (2012) showed an association between carcass traits and fatty acid composition with 91 functional genes in Wagyu x Angus F1 cattle, suggesting that ASB3 can significantly affect the back fat trait. On the other hand, the ERLEC1 gene encodes a resident endoplasmic reticulum (ER) protein that functions in N-glycan recognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The former was 16 bp downstream of an ankyrin repeat and the SOCS box containing 3 (ASB3) gene and 46 bp upstream of the endoplasmic reticulum lectin 1 (ERLEC1) gene. Using the same approach, the study conducted by Zhang et al (2012) showed an association between carcass traits and fatty acid composition with 91 functional genes in Wagyu x Angus F1 cattle, suggesting that ASB3 can significantly affect the back fat trait. On the other hand, the ERLEC1 gene encodes a resident endoplasmic reticulum (ER) protein that functions in N-glycan recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The positional cloning approach considers genes that are located in the neighborhood of previously identified QTL regions. The third method is the comparative approach, which utilizes loci where polymorphisms are known to have a phenotypic effect in one species and explores them as candidates for similar variation in other species (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…“Progress of genome wide association study in domestic animals” published in Journal of Animal Science and Biotechnology 2012 (3:26) [1], is regretfully retracted by the authors due to substantial textual overlap with previously published sources. We apologize to all affected parties for the inconvenience.…”
Section: Retractionmentioning
confidence: 99%
“…GWAS have been used for the first time for the analysis of human diseases, and have become a suitable tool for domestic animals as a result of the development of large collections of SNPs and the large-scale analysis of SNPs at moderate cost (Zhang et al, 2012). The molecular data obtained in GWAS permit the genetic evaluation of young animals for traits of interest in livestock production, such as hot carcass weight (HCW), LEA, and BF.…”
Section: Introductionmentioning
confidence: 99%